1987
DOI: 10.1139/v87-325
|View full text |Cite
|
Sign up to set email alerts
|

The products of the reaction of thiiranium ions with competing nucleophiles

Abstract: The reaction of the stable thiiranium ion, prepared by the reaction of trifluoromethanesulfonic acid and methyl-3-(4-chlorophenylthio)propene with tetraethylammonium chloride in either 3.5 or 36% v/v methanol/dichloromethane with urea as a buffer, forms 2-methoxy-2-methyl-1-propyl 4-chlorophenyl sulfide, 2-chloro-2-methyl-1-propyl 4-chlorophenyl sulfide, and 1-chloro-2-methyl-2-propyl 4-chlorophenyl sulfide as products. While these same products are formed by the addition of 4-chlorobenzenesulfenyl chloride to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The first involves nucleophilic attack at the α-carbon, yielding products 2 and 2′ ( internal nucleophiles give cyclized products), which are themselves useful synthetic building blocks as stereochemical integrity is maintained due to anchimeric assistance by the chalcogen atom ( Path C , Scheme ). ,,, The alternative is nucleophilic attack at the chalcogen center ( Path D , Scheme ) to give an alkene and a highly electrophilic sulfur transfer agent 3 , which may further undergo π-ligand exchange. ,, This reversible process contributes to the limitations of some chalcogen iranium ions in synthesis, particularly for the more electrophilic selenium, as stereochemistry of these species is scrambled. ,,, Investigations into the effects of varying the R group directly on the chalcogen of both thiiranium and seleniranium ions in solution have shown that more bulky groups tend to maintain optical purity, while both electron-donating and -withdrawing groups had minimal impact on the stereo outcome for sulfur substrates. ,,, However, electron-donating groups such as p-OMe-phenyl on the selenium of the iranium ion intermediate lead to extensive scrambling compared to electron-withdrawing groups such as o-NO 2 -phenyl, which maintained stereochemical integrity, a result that was rationalized by the latter activating the α-carbon of the iranium ion toward nucleophilic attack. …”
Section: Introductionmentioning
confidence: 99%
“…The first involves nucleophilic attack at the α-carbon, yielding products 2 and 2′ ( internal nucleophiles give cyclized products), which are themselves useful synthetic building blocks as stereochemical integrity is maintained due to anchimeric assistance by the chalcogen atom ( Path C , Scheme ). ,,, The alternative is nucleophilic attack at the chalcogen center ( Path D , Scheme ) to give an alkene and a highly electrophilic sulfur transfer agent 3 , which may further undergo π-ligand exchange. ,, This reversible process contributes to the limitations of some chalcogen iranium ions in synthesis, particularly for the more electrophilic selenium, as stereochemistry of these species is scrambled. ,,, Investigations into the effects of varying the R group directly on the chalcogen of both thiiranium and seleniranium ions in solution have shown that more bulky groups tend to maintain optical purity, while both electron-donating and -withdrawing groups had minimal impact on the stereo outcome for sulfur substrates. ,,, However, electron-donating groups such as p-OMe-phenyl on the selenium of the iranium ion intermediate lead to extensive scrambling compared to electron-withdrawing groups such as o-NO 2 -phenyl, which maintained stereochemical integrity, a result that was rationalized by the latter activating the α-carbon of the iranium ion toward nucleophilic attack. …”
Section: Introductionmentioning
confidence: 99%
“…The inability of methanol to trap the putative episulfonium ion 8 could indicate that this intermediate is generated as an ion pair that favors attack of hydroxide to yield the alcohol 9a . Examples have been reported in which episulfonium ions are formed as ion pairs that evade reaction with bulk acetic acid ; however, it should be noted that more polar solvents such as the methanol−water mixture employed here typically do not favor such ion pairing . Addition of salts such as lithium perchlorate can disrupt ion pairs, thus allowing reaction of the electrophilic intermediate with solvent ,, .…”
Section: Resultsmentioning
confidence: 94%
“…This assumption is supported by the conversion of 4 with sodium thiomethylate to the doubly ring contracted cis/trans -[12]aneS 4 -(CH 2 SCH 3 ) 2 ( 7 ) (19%; Scheme ): of the two possible regioisomers that could form, the exclusive formation of the one with the relative position of the two methylthio-substituted methylene bridges “anti” to each other was observed (Scheme ). The orientation of the ring opening of the unsymmetrically substituted intermediate 6 depends on (a) steric factors , and (b) the polarity of the solvent . The trans isomer of 7 was obtained by fractional crystallization, and the stereochemistry was assigned on the basis of an X-ray structural analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Heating of 3 in DMF produced pure 5 (94%). From the results discussed above, it emerges that an S−Cl bond (see 8 in Scheme ) or a tight ion-pair (see 9 in Scheme ) is involved in the conversion of intermediate 6 to the products …”
Section: Resultsmentioning
confidence: 99%